Models of lifelong care for children and adolescents with chronic conditions in low-income and middle-income countries: a scoping review. Issue 7 (4th July 2022) - Reif, Lindsey K; van Olmen, Josefien; McNairy, Margaret L; Ahmed, Saeed; Putta, Nande; Bermejo, Raoul; Nugent, Rachel; Paintsil, Elijah; Daelmans, Bernadette; Varghese, Cherian; Sugandhi, Nandita; Abrams, Elaine J
Abstract : Globally, non-communicable diseases (NCDs) or chronic conditions account for one-third of disability-adjusted life-years among children and adolescents under the age of 20. Health systems must adapt to respond to the growing burden of NCDs among children and adolescents who are more likely to be marginalised from healthcare access and are at higher risk for poor outcomes. We undertook a review of recent literature on existing models of chronic lifelong care for children and adolescents in low-income and middle-income countries with a variety of NCDs and chronic conditions to summarise common care components, service delivery approaches, resources invested and health outcomes.